2008
DOI: 10.1016/j.ijmedinf.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the anticipated consequences of Computer-based Provider Order Entry at three community hospitals using an open-ended, semi-structured survey instrument

Abstract: Objective-To determine what "average" clinicians in organizations that were about to implement Computer-based Provider Order Entry (CPOE) were expecting to occur, we conducted an openended, semi-structured survey at three community hospitals. Methods-We created an open-ended, semi-structured, interview survey template that we customized for each organization. This interview-based survey was designed to be administered orally to clinicians and take approximately five minutes to complete, although clinicians wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…In addition, common and consistently applied definitions of medication errors and serious medication errors, as well as consistent stratification of errors by type and/or ordering process stage, will ensure greater comparability across studies. Second, further work is needed to explain variation in findings across studies; for example, authors have noted an increase in medication errors due to CPOE19 and unintended consequences of health IT 2728 Even among the eight studies in our meta-analysis showing reductions in errors due to CPOE, variation in the magnitude of impacts across study settings may indicate that not all patient populations will benefit equally from CPOE's apparent error risk reduction.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, common and consistently applied definitions of medication errors and serious medication errors, as well as consistent stratification of errors by type and/or ordering process stage, will ensure greater comparability across studies. Second, further work is needed to explain variation in findings across studies; for example, authors have noted an increase in medication errors due to CPOE19 and unintended consequences of health IT 2728 Even among the eight studies in our meta-analysis showing reductions in errors due to CPOE, variation in the magnitude of impacts across study settings may indicate that not all patient populations will benefit equally from CPOE's apparent error risk reduction.…”
Section: Discussionmentioning
confidence: 89%
“…Poon and colleagues carried out a mixed-methods study of barriers to CPOE of a diverse sample of hospitals across the US and identified several strategies, including strong leadership and engagement of clinicians, that were integral to successful implementation [17]. Ash, Sittig and colleagues have emphasized both anticipated and unintended consequences of implementation, [18,19] themes echoed by participants in our study.…”
Section: Discussionmentioning
confidence: 95%
“…They suggest that these need to be understood so that they can be prevented or overcome. Sittig et al (2008), in their analysis of consequences of implementing technologies in hospitals, recommend that clinicians must be deeply involved in the selection and implementation process. Both hospitals encouraged extensive user participation in the design of systems that would automate the error-prevention functions.…”
Section: Limitationsmentioning
confidence: 99%